Cryotherapy to treat persistent muscle weakness after joint injury - Kuenze, C.; Hart, J. M. (The Physician and Sportsmedicine, 2010)
Cryotherapy is a widely used modality following acute joint injury. It is considered helpful in reducing pain and swelling, and there is a growing body of evidence to suggest that it may have additional benefits in muscle function. Following joint injury, it is common for patients to experience persistent muscle weakness that is resistant to traditional strengthening exercises. This may be due to a reflex inhibition of musculature surrounding the injured joint. The underlying cause of this reflex inhibition may arise from aberrant sensory information from the joints` neural receptors, which result in a neural inhibition of motor neurons. This inhibition is beyond conscious control, is ongoing, and impedes normal joint function via a disruption of normal muscle function. Cryotherapy treatments targeted at peripheral joints have been shown to result in transient resolution of reflex inhibition, which thereby provide an environment where injured patients can benefit from a more thorough motorneuron pool during controlled rehabilitation exercises. This article presents current evidence-based recommendations regarding the use of joint cryotherapy for maximizing the effectiveness of commonly used rehabilitation exercises in patients recovering from joint injury.